Ready for Europe : public administration reform and European accession in Central and Eastern Europe - Nunberg, Barbara (Washington, DC : World Bank, 2000)
The book defines the performance level countries will need to attain for a range of administrative tasks so the countries may reach a minimal threshold for EU membership. It applies selected standards to determine each country's readiness for accession and for the longer-term transition agenda.
Includes bibliographical references (p. 363-364).
oif 27/10/15
Loan
Keywords: Public administration -- Czech Republic; Public administration -- Poland; Public administration -- Estonia; European Union -- Czech Republic; European Union -- Hungary; European Union -- Estonia